2009
DOI: 10.1007/s00467-009-1243-5
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus infection and haemophagocytosis in a patient with congenital nephrotic syndrome

Abstract: Congenital nephrotic syndrome is a rare clinical entity defined as massive proteinuria leading to symptoms within the infant's first 3 months of life. Although the association between congenital nephrotic syndrome and cytomegalovirus infection has been identified, association with haemophagocytosis has not been reported in the literature. In this case report we describe concomitant cytomegalovirus infection and haemophagocytosis in a 3-month-old girl with congenital nephrotic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…In our study there were non-statistically signi icant differences between CMV IgM positive-patients vs CMV IgM-negative patients (P>0.05) as regarding all blood laboratory investigations (wbcs, platlete, crp, Serum create, Serum albumin, AST, Alt, serum Na, serum K, serum Ca, serum P). However, there were statistically signi icant decreases in HB (P=0.024) and serum urea nitrogen (P=0.04) in IgM positive-patients compared to IgM-negative patients, This also come in agreement with Poyrazoglu et al [13], who studied Cytomegalovirus infection and haemophagocytosis in a patient with congenital nephrotic syndrome in a 3-month-old girl. We concluded that serofrequency of cytomegalovirus infection in pediatric nephrology unit, Zagazig university hospitals during follow-up was 12% for cmv IgM and 100% for cmv IgG at ns children patients.…”
Section: Discussionsupporting
confidence: 87%
“…In our study there were non-statistically signi icant differences between CMV IgM positive-patients vs CMV IgM-negative patients (P>0.05) as regarding all blood laboratory investigations (wbcs, platlete, crp, Serum create, Serum albumin, AST, Alt, serum Na, serum K, serum Ca, serum P). However, there were statistically signi icant decreases in HB (P=0.024) and serum urea nitrogen (P=0.04) in IgM positive-patients compared to IgM-negative patients, This also come in agreement with Poyrazoglu et al [13], who studied Cytomegalovirus infection and haemophagocytosis in a patient with congenital nephrotic syndrome in a 3-month-old girl. We concluded that serofrequency of cytomegalovirus infection in pediatric nephrology unit, Zagazig university hospitals during follow-up was 12% for cmv IgM and 100% for cmv IgG at ns children patients.…”
Section: Discussionsupporting
confidence: 87%
“…Until 2018, 7 cases of CMV-associated CNS were reported in other countries, and CMV infection was the only secondary finding. In the 7 patients, 5 patients underwent renal biopsy (913), and renal tubular cytomegalovirus inclusion bodies were found in 2 patients (9, 10). Of the 7 patients, 5 were administered with antivirus therapy, and proteinuria in 4 patients disappeared, and their clinical conditions improved after ganciclovir treatment (10, 12, 14).…”
Section: Discussionmentioning
confidence: 99%
“…Of the 7 patients, 5 were administered with antivirus therapy, and proteinuria in 4 patients disappeared, and their clinical conditions improved after ganciclovir treatment (10, 12, 14). However, 1 patient died (13). The remaining 2 patients was not administered antivirus therapy; 1 patient improved after symptom-relieving and supportive treatment (10), and the other showed no response to cyclosporin and corticosteroid therapy (11).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic or prolonged infections by several agents, in particular hepatitis B and C, syphilis, toxoplasmosis, AIDS, and cytomegalovirus are some of the causes of secondary nephrotic syndrome 3 , 4 , 5 , 10 , 16 , 20 , 23 , 27 , 28 . On the other hand, frequent use of immunosuppressants in children with kidney disease or kidney transplant recipients make these individuals susceptible to opportunistic infections by intracellular parasites such as cytomegalovirus (CMV) and herpes simplex virus (HSV) 1 or 2 6 , 14 , 21 , 22 .…”
Section: Introductionmentioning
confidence: 99%